Differentiation of Rhodnius neglectus and Rhodnius prolixus (Hemiptera: Reduviidaee: Triatominae) by multiple parameters - Falcone, Rossana [UNESP]; Ribeiro, Aline Rimoldi; Oliveira, Jader de [UNESP]; Mendonca, Vagner Jose; Graminha, Marcia [UNESP]; Rosa, Joao Aristeu da [UNESP] (Soc Brasileira Medicina Tropical, 2020)
Introduction: The genus Rhodnius in the subfamily Triatominae comprises 20 species, which can transmit Trypanosoma cruzi and Trypanosoma rangeli. Due to the development of molecular techniques, Triatominae species can now be characterized by mitochondrial and nuclear markers, making it possible to verify and/or correct the existing data on these species. The results achieved in this study provide a more detailed and accurate differentiation of the Rhodnius species, helping the establishment of a more appropriate classification. Methods: Data collection was performed by DNA analysis, morphological and morphometric studies to distinguish four populations of R. neglectus and four of R. prolixus. Phylogenetic data were compared to morphological and morphomctric data. Results: The analysis of Cytb fragments suggests that the four colonies designated to Rhodnius neglectus as well as those of R. prolixus were correctly identified. Conclusions: The morphological characters observed in the specimens of the colonies originally identified as R. prolixus and R. neglectus, such as the presence or absence of collar in the eggs, the patterns of the median process of the pygophore, and anterolateral angle, are consistent with the species. Geometric morphometrics also show an intraspecific variability in R. prolixus.
Keywords: Taxonomy; Phylogeny; Cytochrome b; Morphology; Geometric morphometrics